International journal of organizational and collective intelligence. - Khosrow-Pour, Mehdi, 1951- (Research in the history of economic thought and methodology., 2012)
Research in the History of Economic Thought and Methodology is an annual series which presents research materials in the fields of the history of economic thought and the methodology of economics. The series is divided in to three types of volumes; A, B & C. With A containing peer-reviewed articles, symposia, and review essays on new works in the history of economic thought and methodology. Volumes B & C contain archival supplements that present previously unpublished materials.